Complications after the percutaneous release of trigger thumb in adults - Aslanturk, Okan; Yilmaz, Ozgur; Ari, Bunyamin; Canbay, Ali; Kavak, Huseyin (Annals of Medical Research, 2021)
Aim: Trigger finger is a common orthopedic problem causing pain and could restrsict daily activities. Surgical intervention can be done via open or percutaneously. There is not much data about minor complications in literature. In this study, we reported our results and complications of percutaneous release (PR) of trigger thumb.Material and Methods: Retrospective data of patients treated for trigger thumb with PR between September 2017 and January 2019 were reviewed. Age, gender, affected side, preoperative Quinnell grade of triggering; previous history of steroid injection and history of medical diseases (e.g. diabetes mellitus, rheumatoid arthritis) were recorded.Results: Thirty thumb of 28 patients who met the inclusion criteria treated with PR for trigger thumb included in the study. Mean age of patients was 53.7 ±9.95 months (range 36-73). Twenty (71%) of patients were female, 8 (29%) were male. Right hand was dominant side in all patients. Right thumb was affected in 18 (64%) patients, left thumb in 8 (29%) and 2 (7%) were bilateral. Due to Quinnell grading system 9 (32%) patients were grade 2 and 19 (68%) were grade 3. Twenty (71%) of patients had previous history of steroid injection. There were 5 complications in our patients. One recurrence of triggering and 4 ecchymosis and edema have been reported.Conclusion: Percutaneous release of trigger thumb is safe and reliable technique with low complication rate. To prevent complication surgeon should be careful during the procedure and should well inform patient what to do after procedure.
Keywords: Histopathology; salivary gland; tumor